Impact of the Seven-valent Pneumococcal Conjugate Vaccine on Acute Otitis Media in Japanese Children: Emergence of Serotype 15A Multidrug-resistant Streptococcus pneumoniae in Middle Ear Fluid Isolates. Issue 9 (September 2015) - Ozawa, Daiki; Yano, Hisakazu; Endo, Shiro; Hidaka, Hiroshi; Kakuta, Risako; Okitsu, Naohiro; Kanamori, Hajime; Ogawa, Miho; Ichimura, Sadahiro; Shimojima, Masahiro; Inomata, Shinya; Kaku, Mitsuo; et al.
Abstract : Background: Streptococcus pneumoniae is one of the most common bacteria causing acute otitis media (AOM). In Japan, a 7-valent pneumococcal conjugate vaccine (PCV7) was introduced for voluntary vaccination of children in 2010, and it became a recommended vaccination in April 2013. We surveyed the serotypes and antimicrobial susceptibility profile of S. pneumoniae isolates obtained from the middle ear fluid of Japanese children with AOM. Methods: Between April and September 2013, a total of 176 S. pneumoniae isolates were obtained from the middle ear fluid of children aged 0–3 years with AOM. Isolates were collected from various regions of Japan. Minimum inhibitory concentrations were measured by the broth microdilution method. Serotyping was performed by observing the Quellung reaction. Results: Although 45.5% of the strains were susceptible to penicillin G, 42.6% were penicillin-intermediate strains and 11.9% were penicillin-resistant strains. Serotype 19A (27.3%), serotype 15A (14.2%) and serotype 3 (11.9%) showed a high frequency. Although PCV7 types only accounted for 4.5% of all strains, 44.9% were PCV13 types and 55.1% were non-PCV types. Serotype 15A strains were 100% nonsusceptible to penicillin G and all of these strains showed multidrug resistance. Serotype 15A was frequent in children up to 1 year old. Conclusion: After this research was completed, PCV7 was switched to a PCV13 that also contained serotype 3 and serotype 19A. We need to consider the possibility that serotype 15A, which is not included in PCV13, may increase and cause intractable AOM in the future.